Strategy for Developing Islamic Education Quality Management in Forming Character and Quality of Student Graduates - Izzati Izzati; Suhendar Sulaeman; Saiful Bahri (International Journal of Educational Narratives, 2024)
Background: Quality management is essential for the continuous development of educational standards. At Muhammadiyah Vocational School in DKI Jakarta, developing Islamic education quality management is key to shaping student character and enhancing the quality of graduates. Purpose: The purpose of this study is to explore strategies for developing Islamic education quality management, focusing on its role in shaping student character and the quality of student graduates. Methods: A descriptive research approach was employed to study the strategies in developing Islamic education quality management. The research utilized the ANP (Analytic Network Process) method to create a model beneficial to the government and society. Data were collected through interviews, observations, and documentation, with validation achieved using triangulation techniques. ANP questionnaires were distributed to gather expert opinions. Results: The research identified key challenges related to human resources, supervision, and facilities at the school. Inadequate supervision and teacher administration were found to be significant issues. Proposed solutions included improvements in teaching practices, salary adjustments, and a restructured school schedule to enhance educational quality. Conclusions: Addressing these issues is essential for improving the quality of education at Muhammadiyah Vocational School. Effective quality management strategies can significantly contribute to the development of student character and the overall quality of graduates.